Analisis Kemampuan Berpikir Aljabar ditinjau dari Self-efficacy - Juan Su, Andromeda Young (Polinomial : Jurnal Pendidikan Matematika, 2025)
Algebraic thinking ability is one of the essential capabilities in mathematics learning, encompassing the ability to understand concepts, utilize algebraic symbols, and solve problems with appropriate strategies. This study aims to identify and describe the algebraic thinking abilities of eighth-grade junior high school students from a self-efficacy perspective. The indicators of algebraic thinking ability in this research refer to concepts proposed by Kieran, which include generalization, transformational, and meta-global levels. Meanwhile, self-efficacy refers to definitions and indicators proposed by Bandura, comprising magnitude, strength, and generality. This research employs a qualitative approach with a case study method involving approximately 27 eighth-grade students from one junior high school through purposive sampling technique. Based on self-efficacy categorization, 6 samples were selected from high, medium, and low categories. The findings of this study reveal how self-efficacy impacts students' responses on algebraic thinking ability tests